2019
DOI: 10.1038/s41598-019-47196-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased similarity of neural responses to experienced and empathic distress in costly altruism

Abstract: Empathy—affective resonance with others’ sensory or emotional experiences—is hypothesized to be an important precursor to altruism. However, it is not known whether real-world altruists’ heightened empathy reflects true self-other mapping of multi-voxel neural response patterns. We investigated this relationship in adults who had engaged in extraordinarily costly real-world altruism: donating a kidney to a stranger. Altruists and controls completed fMRI testing while anticipating and experiencing pain, and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 70 publications
8
25
2
Order By: Relevance
“…The second sub-system comprised regions commonly involved in representing and empathizing with the distress of others, and included the dorsal ACC, pre-SMA, and anterior insula (Ashar et al, 2017; Decety & Lamm, 2006; Lamm et al, 2011). Activation in these regions emerged only during altruistic decisions, consistent with the theory that affective resonance with others’ distress give rise to empathic concern and altruistic motivation, which is a primary motivator of prosocial behavior in the absence of cooperative or equity-maintaining goals (Batson, 2009, 2011; Brethel-Haurwitz et al, 2018; Decety et al, 2016; O’Connell et al, 2019). This finding was likely driven by eight out of the fourteen identified altruistic studies including stimuli that depicted or implied the need or distress of beneficiaries.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The second sub-system comprised regions commonly involved in representing and empathizing with the distress of others, and included the dorsal ACC, pre-SMA, and anterior insula (Ashar et al, 2017; Decety & Lamm, 2006; Lamm et al, 2011). Activation in these regions emerged only during altruistic decisions, consistent with the theory that affective resonance with others’ distress give rise to empathic concern and altruistic motivation, which is a primary motivator of prosocial behavior in the absence of cooperative or equity-maintaining goals (Batson, 2009, 2011; Brethel-Haurwitz et al, 2018; Decety et al, 2016; O’Connell et al, 2019). This finding was likely driven by eight out of the fourteen identified altruistic studies including stimuli that depicted or implied the need or distress of beneficiaries.…”
Section: Discussionsupporting
confidence: 80%
“…Recent work has focused on making neuroimaging paradigms more “naturalistic,” such as viewing or listening to narratives or interacting in real-time with another person in the laboratory (Hasson & Frith, 2016; Redcay & Moraczewski, 2019; Redcay & Schilbach, 2019; Wheatley et al, 2019) or in the real-world (Dikker et al, 2019). Other work has concentrated on characterizing the behavioral and neural features of individuals who engage in extreme forms of real-world prosociality (Brethel-Haurwitz et al, 2018; Marsh et al, 2014; O’Connell et al, 2019; Vekaria et al, 2020). Understanding the neurobiology underlying more ecologically-valid altruistic decisions will be crucial for understanding the broader picture of prosocial decision-making.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] . Remarkably, these activity patterns are highly similar to those measured when pain is experienced directly by oneself [15][16][17][18][19][20][21][22] , and they are attenuated by those same analgesic procedures that regulate first-hand nociception, such as placebo or hypnosis 17,23,24 . These results suggest that others' pain is at least partly processed in an embodied (or empathetic) fashion, that is, by simulating its somatic and affective properties on one's own body 25,26 .…”
Section: Introductionsupporting
confidence: 52%
“…Previous studies have reported how AI and middle cingulate cortex (MCC) respond to others' suffering [8][9][10][11][12][13][14] , as conveyed through facial expressions 4,20,21,23,24 , photos/videos of injuries 15,17,18,21,27,28,35,38,50 , symbolic cues 16,19,22,51 , and short narratives 34,36,[42][43][44][45] . Yet the functional interpretation of these neural responses remains debated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation